Круглый стол "Общество и социология на пороге третьего тысячелетия" (Социология: теория, методы, маркетинг, 1999)
On March 19, 1999, Institute of Sociology of the NAS of Ukraine, Sociologic Association of Ukraine, and “Sociology: Theory, Methods, Marketing” journal organized and conducted round table “Society and Sociology at the edge of Third Millennium” where leading Ukrainian sociologists discussed current situation and tends of society development, the contribution of sociologic science, in particular, national, to current social research.